Restrictive vs. Liberal Red Blood Cell Transfusion Strategy in Patients With Acute Myocardial Infarction and Anemia: A Systematic Review and Meta-Analysis - Zhang, Yeshen; Xu, Zhengrong; Huang, Yuming; Ye, Qirao; Xie, Nianjin; Zeng, Lihuan; Lian, Xingji; Dai, Yining; Chen, Jiyan; He, Pengcheng; Tan, Ning; Liu, Yuanhui (Frontiers in Cardiovascular Medicine, 2021)
Objective: Anemia is frequent in patients with acute myocardial infarction (AMI), and the optimal red blood cell transfusion strategy for AMI patients with anemia is still controversial. We aimed to compare the efficacy of restrictive and liberal red cell transfusion strategies in AMI patients with anemia. Methods: We systematically searched PubMed, EMBASE, Web of Science, Cochrane Library, and Clinicaltrials.gov, from their inception until March 2021. Studies designed to compare the efficacy between restrictive and liberal red blood cell transfusion strategies in patients with AMI were included. The primary outcome was all-cause mortality, including overall mortality, in-hospital or follow-up mortality. Risk ratios (RR) with 95% confidence intervals (CI) were presented and pooled by random-effects models. Results: The search yielded a total of 6,630 participants in six studies. A total of 2,008 patients received restrictive red blood cell transfusion while 4,622 patients were given liberal red blood cell transfusion. No difference was found in overall mortality and follow-up mortality between restrictive and liberal transfusion groups (RR = 1.07, 95% CI = 0.82–1.40, P = 0.62; RR = 0.89, 95% CI = 0.56–1.42, P = 0.62). However, restrictive transfusion tended to have a higher risk of in-hospital mortality compared with liberal transfusion (RR = 1.22, 95% CI = 1.00–1.50, P = 0.05). No secondary outcomes, including follow-up reinfarction, stroke, and acute heart failure, differed significantly between the two groups. In addition, subgroup analysis showed no differences in overall mortality between the two groups based on sample size and design. Conclusion: Restrictive and liberal red blood cell transfusion have a similar effect on overall mortality and follow-up mortality in AMI patients with anemia. However, restrictive transfusion tended to have a higher risk of in-hospital mortality compared with liberal transfusion. The findings suggest that transfusion strategy should be further evaluated in future studies.